Aspects of the Psychological Well-being of Muslim Students in Bandung from the Perspective of Islamic Psychology during the Covid-19 Pandemic - Ecep Supriatna; Muhammad Rezza Septian; Tuti Alawiyah (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
This article aims to explore aspects of the psychological well-being of Muslim students in Bandung during the Covid19 pandemic from the perspective of Islamic psychology. This study uses a quantitative approach with a survey method. The research participants consisted of 576 Muslim students in Bandung. Data were collected using a psychological well-being instrument developed by Ryff. The data analysis technique used is factor analysis. Based on the results of the study, it was obtained that the dominant aspects of psychological well being were ranked, namely positive relations with others at 74.1%; second, purpose in life by 73.2%; third, self-acceptance of 71.5%; fourth, autonomy of 71.4%; fifth, environmental mastery of 70.1% and the sixth, personal growth of 69.8%.Artikel ini bertujuan untuk mengeksplorasi aspek-aspek kesejahteraan psikologis pada mahasiswa muslim di kota Bandung selama pandemi Covid19. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survey. Partisipan penelitian terdiri dari 576 mahasiswa beragama Islam di kota Bandung dan Cimahi. Data dikumpulkan menggunakan instrumen kesejahteraan psikologis yang dikembangkan oleh Ryff. Teknik analisis data yang digunakan yaitu analisis faktor. Berdasarkan hasil penelitian diperoleh peringkat aspek-aspek yang dominan terhadap psychological well being yaitu: Pertama positive relations with others sebesar 74.1%; Kedua, purpose in life sebesar 73.2%; Ketiga,  self-acceptance sebesar 71.5%; Keempat, autonomy sebesar 71.4%; Kelima, environmental mastery sebesar 70.1%; dan Keenam, personal growth sebesar 69.8%.